2021
DOI: 10.1017/s0007114521001239
|View full text |Cite
|
Sign up to set email alerts
|

Long-term chronic caloric restriction alters miRNA profiles in the brain of ageing mice

Abstract: Calorie restriction (CR) has been shown to be one of the most effective methods in alleviating the effects of ageing and age-related diseases such as increasing longevity and preventing dementia, and Alzheimer’s Disease. Although the protective effects of CR have been reported, the exact molecular mechanism still needs to be clarified. This study aims to determine differentially expressed (DE) miRNAs and altered gene pathways due to long-term chronic (CCR) and intermittent (ICR) CR in the brain of mice to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
(12 reference statements)
0
2
0
1
Order By: Relevance
“…The abnormal regulation of miRNA may participate in the progression of the disease by affecting the expression and function of target genes [ 43 ]. MiR-184 has been shown to play a role in neurogenesis, chromatin, and histone regulation, which may be a potential target for neurodegenerative diseases [ 44 ]. This study showed that the levels of miR-184 in urinary exosomes from PD patients were significantly higher than those of matched healthy control subjects, which were inconsistent with the plasma miR-184 levels in PD patients reported by Na Li et al [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal regulation of miRNA may participate in the progression of the disease by affecting the expression and function of target genes [ 43 ]. MiR-184 has been shown to play a role in neurogenesis, chromatin, and histone regulation, which may be a potential target for neurodegenerative diseases [ 44 ]. This study showed that the levels of miR-184 in urinary exosomes from PD patients were significantly higher than those of matched healthy control subjects, which were inconsistent with the plasma miR-184 levels in PD patients reported by Na Li et al [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…NK cell aging [282,283] , age-related loss of muscle cells [284] , and skeletal cell aging [285] ; downregulated in peripheral blood and associated with all-cause mortality and agerelated traits [286] 7 miR-184 Downregulated in calorie-restricted mouse brain [287] , older adults with major depressive disorder [288] , downregulated in aging heart [278] 8 miR-222-5p…”
Section: Mir-200cmentioning
confidence: 99%
“…Таким образом, по мнению авторов, режим CCR может оказывать защитные эффекты, модулируя специфические miRNA, поскольку они играют роль в нейрогенезе, регуляции хроматина и гистонов. Эти три группы miRNA могут быть потенциальными мишенями для нейродегенеративных и связанных со старением заболеваний и могут играть важную роль в защитных эффектах ограничения калорийности пищи в головном мозге [106].…”
Section: Reviewunclassified